2019
DOI: 10.1002/jcu.22774
|View full text |Cite
|
Sign up to set email alerts
|

Portal venous gas by ultrasound in advance of impending necrotizing enterocolitis of a very low birth weight infant

Abstract: Necrotizing enterocolitis (NEC) is a serious complication of premature infants, portal venous gas (PVG) under X‐ray, and ultrasound is a typical manifestation of this disease. We report a case of a very low birth weight (VLBW) infant with PVG unexpectedly detected by ultrasound before the onset of NEC. After positive ultrasound result, clinical manifestations, X‐ray, and lab tests confirmed the diagnosis of NEC. This is the first report of a similar case, demonstrating the value of ultrasonography in predictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The portal venous gas(PVG) observedby X-ray or sonographic imagingis also considered as a typicaldiagnostic feature of confirmed necrotizing enterocolitis. Some data reported that PVG can be a predictive diagnosis for the onset of NEC, which was first identified by Yue et al, who discovered the occurrence of portal gas before the onset of NEC (12) .…”
Section: Discussionmentioning
confidence: 96%
“…The portal venous gas(PVG) observedby X-ray or sonographic imagingis also considered as a typicaldiagnostic feature of confirmed necrotizing enterocolitis. Some data reported that PVG can be a predictive diagnosis for the onset of NEC, which was first identified by Yue et al, who discovered the occurrence of portal gas before the onset of NEC (12) .…”
Section: Discussionmentioning
confidence: 96%
“…Portal venous gas (PVG) was an important clinical sign in stage II or III NEC in preterm neonates. The detection of PVG on abdominal ultrasound (AUS) (as opposed to on X-ray examination) was proven to be as early sign of impending NEC in VLBW neonates ( 7 ), and sonographic findings of PVG (OR = 3.9) were significantly associated with surgery and/or death ( 8 ). Moreover, PVG was detected by the AUS with high specificity (86–100%) and proper sensitivity (3–45%) in the diagnostic value of NEC in preterm neonates ( 9 ).…”
Section: Introductionmentioning
confidence: 99%